2006
DOI: 10.1063/1.2216487
|View full text |Cite
|
Sign up to set email alerts
|

Electromigration and critical product in eutectic SnPb solder lines at 100°C

Abstract: Due to a significant change in electromigration behavior of eutectic SnPb at different temperatures, it is critical to understand it at the device temperature, i.e., 100°C. In the present study, the electromigration behavior of e-SnPb is investigated at 100°C and at different current densities, varying within the range of 5×103–5×104A∕cm2. The test samples are prepared by reflowing solder into V grooves etched on (001) Si wafers. The electromigration is observed at the current densities higher than 1×104A∕cm2.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(5 citation statements)
references
References 12 publications
1
4
0
Order By: Relevance
“…By contrast, Pb atoms had a tendency to migrate to the chip side in joint 8. Generally, most Pb atoms migrated in the direction of electron flow, which agrees well with the findings by other researchers [1,11]. Fig.…”
Section: Resultssupporting
confidence: 92%
“…By contrast, Pb atoms had a tendency to migrate to the chip side in joint 8. Generally, most Pb atoms migrated in the direction of electron flow, which agrees well with the findings by other researchers [1,11]. Fig.…”
Section: Resultssupporting
confidence: 92%
“…This was also supported by later findings in EM experiments above 100°C [11,12]. In the case of EM at 100°C, Agarwal et al examined the EM behavior and identified that Pb is still the dominant diffusion species [13]. Compared to the results above, EM tests were carried out at room temperature by Liu et al [14].…”
Section: Phase Separation and Atomic Transport Under Current Stressingmentioning
confidence: 64%
“…Most Pb atoms migrated in the direction of electron flow, which agrees well with the findings of other researchers. 2,[15][16][17][18] In addition, a tilting effect of the current during the electromigration process 6,19,20 can be observed from Fig. 4.…”
Section: Resultsmentioning
confidence: 88%